Serum cadmium positively correlates with inflammatory cytokines in patients with chronic obstructive pulmonary disease. Issue 1 (15th October 2021) - Jiang, Ya‐Lin; Fei, Jun; Cao, Peng; Zhang, Chen; Tang, Min‐Min; Cheng, Jia‐Yi; Zhao, Hui; Fu, Lin
Abstract: Background: Cadmium is a ubiquitous toxic heavy metal and environmental toxicant. Inflammation exerts central roles in the process of chronic obstructive pulmonary disease (COPD). However, few epidemiological studies on the correlation between cadmium exposure and COPD are available. The aim of this study was to evaluate the correlations among serum cadmium, inflammatory cytokines and pulmonary function in COPD patients. Methods: All 940 COPD patients were finally recruited in this study. Demographic characteristics and clinical information were extracted. Fasting serum was collected. Serum cadmium was detected through graphite furnace atomic absorption spectrophotometry. Serum inflammatory cytokines were measured using enzyme‐linked immunosorbent assay. Results: All patients were classified into three groups according to the tertile division of serum cadmium concentration: low (<0.77 μg/L, L), medium (0.77–1.01 μg/L, M), and high (1.01 μg/L, H). Logistic regression analysis found that serum cadmium was inversely correlated with pulmonary function before and after adjusted confounding variables. When stratified by gender, serum cadmium was still negatively correlated with pulmonary function in COPD patients. Moreover, higher serum cadmium elevated CAT (COPD Assessment Test) score before and after adjusted confounding variables. Though a non‐linear association between serum cadmium and inflammatory cytokines, serum cadmium was positively associated with inflammatory cytokines (TNF‐α and MCP‐1). TNF‐α and MCP‐1 exerted a partial mediator in the association between cadmium exposure and pulmonary function decline in COPD patients. Conclusions: Serum cadmium concentration is inversely correlated with pulmonary function among COPD patients. Inflammatory cytokines may be important mediators for cadmium‐induced pulmonary function decline in COPD patients.